Improving chronology for Aotearoa New Zealand: New research in tree-ring derived radiocarbon and stable isotope time series - Gretel Boswijk; Neil J. Loader; Alan Hogg; Luitgard Schwendenmann; Melanesia Boseren; Dilys Johns (Dendrochronologia, 2025)

Resolving challenges in the development of a protocol for δ 18 O determinations on tree-ring cellulose - John du Plessis; Dipayan Paul; Margot Kuitems; Anita Aerts-Bijma; Neil J. Loader; Harro A.J. Meijer; Michael Dee (Isotopes in Environmental and Health Studies, 2025)

ISODATE – Software for stable isotope dendrochronology - Darren Davies; Neil J. Loader; Danny McCarroll; Dan Miles; Christopher Bronk Ramsey (Dendrochronologia, 2025)

Beyond maximum density: multi-parameter insights into Scots pine climate sensitivity - Inga K. Homfeld; Frederick Reinig; Edurne Martinez del Castillo; Max C. A. Torbenson; Oliver Konter; Rob Wilson; Paul J. Krusic; Neil J. Loader; Hakan Grudd; Emily Reid; Kayleigh Letherbarrow; Jan Esper (Trees, 2025)
Key message Climate sensitivity of Pinus sylvestris has changed in minimum density while maximum density remains mostly stable, suggesting the use of additional density parameters could help detect response changes. Abstract As one of Eurasia's most widely distributed conifer species, Pinus sylvestris L. is frequently used in dendroclimatological reconstructions based on tree-ring width (TRW) and maximum latewood density (MXD). However, the climatic signals of additional parameters such as earlywood/latewood density (EWD/LWD) or minimum density (MND) are often overlooked, leaving their skill unexplored. Here, we investigate the growth responses of multiple P. sylvestris tree-ring parameters to ongoing climate change at two sites with contrasting climatic conditions using well-replicated density data from Scotland and Sweden. Correlations with mean, minimum, and maximum temperatures are strongest for LWD and MXD at both sites, with coefficients ranging from 0.5 to 0.7 for July, August, and the June–August season ( p < 0.05). A significant ( p < 0.05) negative correlation between MND and July temperatures was identified in the Swedish Torneträsk (TOR) data ( p < 0.05), which diminished since the late twentieth century. A comparable inverse MND temperature signal and change into the twenty-first century is not reflected in northern Scotland’s overall wetter and warmer site, suggesting a fundamental physiological change in tree-ring formation under global warming. A shift in the sensitivity of tree growth at northern European sites could reduce the effectiveness of proxies from such locations, posing implications for high-resolution climate reconstructions.

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Oxygen isotope dendrochronology allows dating of historical timbers across a wide geographical region - Kristof Haneca; Vincent Debonne; Darren Davies; Danny McCarroll; Neil J. Loader (Dendrochronologia, 2025)

Evaluation of the non-climatic (age-related) trends of stable oxygen and carbon isotopes in Swiss stone pine (Pinus cembra L.) tree rings from the Eastern Carpathians, Romania - Zoltan Kern; Viorica Nagavciuc; István Gábor Hatvani; István Norbert Hegyi; Neil J. Loader; Ionel Popa (Dendrochronologia, 2023)

Climatic controls on the survival and loss of ancient types of barley on North Atlantic Islands - Peter Martin; Terence A. Brown; Timothy S. George; Björn Gunnarson; Neil J. Loader; Paul Ross; John Wishart; Rob Wilson (Climatic Change, 2023)
For ancient types of barley at sites in the Scottish Isles, Faroes, and Iceland, we calculated minimum temperature requirements for grain production (grain production threshold, GPT) as accumulated degree days over the cropping season. Site suitability for barley from AD 1200 to 2000 was investigated by comparing these thresholds with reconstructions of annual cropping season degree days (CSDD) using temperature and tree-ring data. In Iceland, between AD 1200 and 1500, reconstructed CSDD were more favorable in the southwest (Reykjavik), with fewer years below the GPT, than in the North, East and West, but there were two periods (1340–1389 and 1426–1475) with low average CSDD and several years below the GPT which possibly influenced the abandonment of barley cultivation around this time. Reconstructed CSDD for the Faroes (Tórshavn) had only one year below the GPT, but 15 periods of four or more consecutive years with low CSDD which would have challenged barley cultivation, especially in the thirteenth century. Reconstructed CSDD were highest for the Scottish Isles, allowing a more prominent role of barley in the farming system and economy. Nevertheless, years with poor harvests or famines were common and about half were associated with low CSDD, resulting in a significant temperature link but also demonstrating the important contribution of other factors. Despite frequent unfavorable years in both the Faroes and Scottish Isles, resilient production systems, well-adapted barley strains and socio-economic factors allowed barley cultivation to continue, and some ancient types to survive to the present day.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Summer precipitation for the England and Wales region, 1201–2000 ce , from stable oxygen isotopes in oak tree rings - Neil J. Loader; Giles H. F. Young; Danny McCarroll; Darren Davies; Daniel Miles; Christopher Bronk Ramsey (Journal of Quaternary Science, 2020)
Oxygen isotope ratios from oak tree rings are used to extend the May–August precipitation totals of the England and Wales precipitation series back to 1201 ce. The agreement between instrumental and reconstructed values is unusually strong, with more than half of the variance explained and standard verification tests passed. The stability of this relationship is confirmed using split‐period calibration and verification. This allows the reconstruction to be variance‐scaled to the full length of the instrumental series back to 1766. Direct comparison with historical reports of very wet and dry summers show good agreement. Near‐constant replication, with a minimum of 10 timbers sourced from historic buildings across central southern England ensures signal strength does not change over time. Summers during the late 20th century appear anomalously dry and those of the 21st century very close to the pre‐20th century average with no evidence in the record of prolonged ‘megadroughts’ across England and Wales.

Traces of volcanic ash from the Mediterranean, Iceland and North America in a Holocene record from south Wales, UK - Gwydion Jones; Siwan M. Davies; Richard A. Staff; Neil J. Loader; Sarah J. Davies; Michael J. C. Walker (Journal of Quaternary Science, 2020)
A tephra record is presented for a sediment core from Llyn Llech Owain, south Wales, spanning the early‐ to mid‐Holocene. Seven cryptotephra deposits are discovered with three thought to correlate with known eruptions and the remaining four considered to represent previously undocumented events. One deposit is suggested to correlate with the ~6.9 cal ka bp Lairg A tephra from Iceland, whereas more distant sources are proposed as the origin for two of the tephra deposits. A peak of colourless shards in early‐Holocene sediments is thought to tentatively correlate with the ~9.6 cal ka bp Fondi di Baia tephra (Campi Flegrei) and a second cryptotephra is tentatively correlated with the ~3.6 cal ka bp Aniakchak (CFE) II tephra (Alaska). The Fondi di Baia tephra has never been recorded beyond proximal sites and its discovery in south Wales significantly extends the geographical distribution of ash from this eruption. The remaining four cryptotephra deposits are yet to be correlated with known eruptions, demonstrating that our current understanding of widespread tephra deposits is incomplete. This new tephra record highlights the potential for sites at more southerly and westerly locations in northwest Europe to act as repositories for ash from several volcanic regions.

Spatio‐temporal patterns of tree growth as related to carbon isotope fractionation in European forests under changing climate - Tatiana A. Shestakova; Jordi Voltas; Matthias Saurer; Frank Berninger; Jan Esper; Laia Andreu‐Hayles; Valérie Daux; Gerhard Helle; Markus Leuenberger; Neil J. Loader; Valérie Masson‐Delmotte; Antonio Saracino; et al. (Global Ecology and Biogeography, 2019)
Aim The aim was to decipher Europe‐wide spatio‐temporal patterns of forest growth dynamics and their associations with carbon isotope fractionation processes inferred from tree rings as modulated by climate warming. Location Europe and North Africa (30‒70° N, 10° W‒35° E). Time period 1901‒2003. Major taxa studied Temperate and Euro‐Siberian trees. Methods We characterize changes in the relationship between tree growth and carbon isotope fractionation over the 20th century using a European network consisting of 20 site chronologies. Using indexed tree‐ring widths (TRW i ), we assess shifts in the temporal coherence of radial growth across sites (synchrony) for five forest ecosystems (Atlantic, boreal, cold continental, Mediterranean and temperate). We also examine whether TRW i shows variable coupling with leaf‐level gas exchange, inferred from indexed carbon isotope discrimination of tree‐ring cellulose (Δ 13 C i ). Results We find spatial autocorrelation for TRW i and Δ 13 C i extending over a maximum of 1,000 km among forest stands. However, growth synchrony is not uniform across Europe, but increases along a latitudinal gradient concurrent with decreasing temperature and evapotranspiration. Latitudinal relationships between TRW i and Δ 13 C i (changing from negative to positive southwards) point to drought impairing carbon uptake via stomatal regulation for water saving occurring at forests below 60° N in continental Europe. An increase in forest growth synchrony over the 20th century together with increasingly positive relationships between TRW i and Δ 13 C i indicate intensifying impacts of drought on tree performance. These effects are noticeable in drought‐prone biomes (Mediterranean, temperate and cold continental). Main conclusions At the turn of this century, convergence in growth synchrony across European forest ecosystems is coupled with coordinated warming‐induced effects of drought on leaf physiology and tree growth spreading northwards. Such a tendency towards exacerbated moisture‐sensitive growth and physiology could override positive effects of enhanced leaf intercellular CO 2 concentrations, possibly resulting in Europe‐wide declines of forest carbon gain in the coming decades.

Tree ring dating using oxygen isotopes: a master chronology for central England - Neil J. Loader; Danny Mccarroll; Daniel Miles; Giles H. F. Young; Darren Davies; Christopher Bronk Ramsey (Journal of Quaternary Science, 2019)
Ring‐width dendrochronology, based on matching patterns of ring width variability, works best when trees are growing under significant environmental (climatic) stress. In the UK, and elsewhere in the temperate mid‐latitudes, trees generally experience low stress, so dating is more difficult and often fails. Oxygen isotopes in tree rings passively record changes in the isotopic ratios of summer precipitation, so they carry a strong common signal, which offers potential for cross‐dating. A master chronology covering the period 1200–2000 ce was constructed using the oxygen isotope ratios of the latewood cellulose of oak samples from central England. Two independent chronologies, developed to verify the isotopic signal, were combined ( n = 10 trees) and the method was evaluated by dating timbers of known age and historical timbers that could not be dated by ring‐width dendrochronology, from both within and beyond the central England region. The agreement between samples and the master chronology is exceptionally strong, allowing the dating of timbers with far fewer rings than is normally the case for ring‐width dendrochronology. Tree‐ring oxygen isotope values are more suited to correlation analysis than tree‐ring widths, so it is possible to provide t ‐values that conform to Student's t ‐distribution and can be converted into probabilities of error. A protocol for assigning dates using ‘stable‐isotope dendrochronology’ is proposed, which has the potential to revolutionize the dating of wooden structures and artefacts, allowing the dating of short and invariant ring sequences from young, fast‐grown trees. Such samples are commonplace throughout the historical building and archaeological records and were, until now, considered impossible to date. © 2019 The Authors. Journal of Quaternary Science Published by John Wiley & Sons Ltd

Stable oxygen isotopes in Romanian oak tree rings record summer droughts and associated large-scale circulation patterns over Europe - Viorica Nagavciuc; Monica Ionita; Aurel Perșoiu; Ionel Popa; Neil J. Loader; Danny McCarroll (Climate Dynamics, 2019)

Reconstructing 800 years of summer temperatures in Scotland from tree rings - Miloš Rydval; Neil J. Loader; Björn E. Gunnarson; Daniel L. Druckenbrod; Hans W. Linderholm; Steven G. Moreton; Cheryl V. Wood; Rob Wilson (Climate Dynamics, 2017)

Spatial reconstruction of Scottish summer temperatures from tree rings - Miloš Rydval; Björn E. Gunnarson; Neil J. Loader; Edward R. Cook; Daniel L. Druckenbrod; Rob Wilson (International Journal of Climatology, 2017)
A detailed understanding of past temporal patterns and spatial expression of temperature variations is important to place recent anthropogenic climate change into a longer term context. In order to fill the current gap in our understanding of northwest European temperature variability, point‐by‐point principal component regression was used to reconstruct a spatial field of 0.5° temperature grids across Scotland. A sequence of reconstructions utilizing several combinations of detrending and disturbance correction procedures, and a selection of tree‐ring parameters [including ring width ( RW ), maximum latewood density ( MXD ) and blue intensity ( BI )] was used in an evaluation of reconstruction skill. The high resolution of the reconstructed field serves also as a diagnostic tool to spatially assess the temperature reconstruction potential of local chronologies. Best reconstruction results, reaching calibration r 2 = 65.8% and verification r 2 = 63.7% in central Scotland over the 1901–1976 period, were achieved using disturbance‐corrected and signal‐free detrended RW chronologies merged with BI data after low‐pass (high‐pass) filtering the RW ( BI ) chronologies. Calibration and verification r 2 > 50% was attained for central, north and east Scotland, >40% in west and northwest, and >30% in southern Scotland with verification of nearly all grids showing some reconstruction skill. However, the full calibration potential of reconstructions outside central Scotland was reduced either due to residual disturbance trends undetected by the disturbance correction procedure or due to other climatic or non‐climatic factors which may have adversely affected the strength of the climate signal.

Oxygen stable isotope ratios from British oak tree-rings provide a strong and consistent record of past changes in summer rainfall - Giles H. F. Young; Neil J. Loader; Danny McCarroll; Roderick J. Bale; Joanne C. Demmler; Daniel Miles; Nigel T. Nayling; Katja T. Rinne; Iain Robertson; Camilla Watts; Matthew Whitney (Climate Dynamics, 2015)

Spatial variability and temporal trends in water‐use efficiency of European forests - Matthias Saurer; Renato Spahni; David C. Frank; Fortunat Joos; Markus Leuenberger; Neil J. Loader; Danny McCarroll; Mary Gagen; Ben Poulter; Rolf T.W. Siegwolf; Laia Andreu‐Hayles; Tatjana Boettger; et al. (Global Change Biology, 2014)
The increasing carbon dioxide (CO 2 ) concentration in the atmosphere in combination with climatic changes throughout the last century are likely to have had a profound effect on the physiology of trees: altering the carbon and water fluxes passing through the stomatal pores. However, the magnitude and spatial patterns of such changes in natural forests remain highly uncertain. Here, stable carbon isotope ratios from a network of 35 tree‐ring sites located across Europe are investigated to determine the intrinsic water‐use efficiency ( iWUE ), the ratio of photosynthesis to stomatal conductance from 1901 to 2000. The results were compared with simulations of a dynamic vegetation model (LPX‐Bern 1.0) that integrates numerous ecosystem and land–atmosphere exchange processes in a theoretical framework. The spatial pattern of tree‐ring derived iWUE of the investigated coniferous and deciduous species and the model results agreed significantly with a clear south‐to‐north gradient, as well as a general increase in iWUE over the 20th century. The magnitude of the iWUE increase was not spatially uniform, with the strongest increase observed and modelled for temperate forests in Central Europe, a region where summer soil‐water availability decreased over the last century. We were able to demonstrate that the combined effects of increasing CO 2 and climate change leading to soil drying have resulted in an accelerated increase in iWUE . These findings will help to reduce uncertainties in the land surface schemes of global climate models, where vegetation–climate feedbacks are currently still poorly constrained by observational data.

A 520 year record of summer sunshine for the eastern European Alps based on stable carbon isotopes in larch tree rings - Polona Hafner; Danny McCarroll; Iain Robertson; Neil J. Loader; Mary Gagen; Giles HF Young; Roderick J. Bale; Eloni Sonninen; Tom Levanič (Climate Dynamics, 2014)

Testate amoebae as a proxy for reconstructing Holocene water table dynamics in southern Patagonian peat bogs - SIMON VAN BELLEN; DMITRI MAUQUOY; RICHARD J. PAYNE; THOMAS P. ROLAND; TIM J. DALEY; PAUL D. M. HUGHES; NEIL J. LOADER; F. ALAYNE STREET‐PERROTT; EMMA M. RICE; VERÓNICA A. PANCOTTO (Journal of Quaternary Science, 2014)
Testate amoebae are abundant and diverse in Sphagnum peat bogs and have been used extensively as indicators of past water table depths. Although these unicellular protists are widely dispersed with globally similar hydrological preferences, regional variations in communities demand region‐specific transfer functions. Here we present the first transfer function for southern Patagonian bogs, based on 154 surface samples obtained from transects in five bogs sampled in 2012 and 2013. Significant variance was explained by pH, electrical conductivity and, in particular, water table depth. Transfer functions for water table were constructed using weighted averaging and evaluated by cross‐validation and independent test sets. The optimal transfer function has predictive ability, but relatively high prediction errors given the wide range in sampled water tables. The use of independent test sets, as well as cross‐validation, allows a more rigorous assessment of model performance than most previous studies. For a subset of locations we compare surface and subsurface samples to demonstrate significant differences in community composition, possibly due to vertical zonation. Our results provide the first quantification of hydrological optima and tolerances for several rare species, which may include Southern Hemisphere endemics and pave the way for palaeohydrological reconstructions in southern Patagonian bogs.

Hydrology and climatology at Laguna La Gaiba, lowland Bolivia: complex responses to climatic forcings over the last 25 000 years - SARAH E. METCALFE; BRONWEN S. WHITNEY; KATHARINE A. FITZPATRICK; FRANCIS E. MAYLE; NEIL J. LOADER; F. ALAYNE STREET‐PERROTT; DAVID G. MANN (Journal of Quaternary Science, 2014)
Diatom, geochemical and isotopic data provide a record of environmental change in Laguna La Gaiba, lowland Bolivia (17°45′S, 57°35′W), over the last ca. 25 000 years. High‐resolution diatom analysis around the Last Glacial–Interglacial Transition provides new insights into this period of change. The full and late glacial lake was generally quite shallow, but with evidence of periodic flooding. At about 13 100 cal a BP, just before the start of the Younger Dryas chronozone, the diatoms indicate shallower water conditions, but there is a marked change at about 12 200 cal a BP indicating the onset of a period of high variability, with rising water levels punctuated by periodic drying. From ca. 11 800 to 10 000 cal a BP, stable, deeper water conditions persisted. There is evidence for drying in the early to middle Holocene, but not as pronounced as that reported from elsewhere in the southern hemisphere tropics of South America. This was followed by the onset of wetter conditions in the late Holocene consistent with insolation forcing. Conditions very similar to present were established about 2100 cal a BP. A complex response to both insolation forcing and millennial‐scale events originating in the North Atlantic is noted.

Comparing the performance of different stomatal conductance models using modelled and measured plant carbon isotope ratios (δ 13 C): implications for assessing physiological forcing - Per E. Bodin; Mary Gagen; Danny McCarroll; Neil J. Loader; Risto Jalkanen; Iain Robertson; Vincent R Switsur; John S. Waterhouse; Ewan J. Woodley; Giles H. F. Young; Paul B. Alton (Global Change Biology, 2013)
Accurate modelling of long‐term changes in plant stomatal functioning is vital to global climate change studies because changes in evapotranspiration influence temperature via physiological forcing of the climate. Various stomatal models are included in land surface schemes, but their robustness over longer timescales is difficult to validate. We compare the performance of three stomatal models, varying in their degree of complexity, and coupled to a land surface model. This is carried out by simulating the carbon isotope ratio of tree leaves (δ 13 C leaf ) over a period of 53 years, and comparing the results with carbon isotope ratios obtained from tree rings (δ 13 C stem ) measured at six sites in northern Europe. All three stomatal models fail to capture the observed interannual variability in the measured δ 13 C stem time series. However, the Soil‐Plant‐Atmosphere ( SPA ) model performs significantly better than the Ball‐Berry ( BB ) or COX models when tested for goodness‐of‐fit against measured δ 13 C stem . The δ 13 C leaf time series simulated using the SPA model are significantly positively correlated ( P SPA model underestimates interannual variability measured in δ 13 C stem , but is no worse than the BB model and significantly better than the COX model. The inability of current models to adequately replicate changes in stomatal response to rising levels of CO 2 concentrations, and thus to quantify the associated physiological forcing, warrants further investigation.

A millennial long March–July precipitation reconstruction for southern-central England - Rob Wilson; Dan Miles; Neil J. Loader; Tom Melvin; Laura Cunningham; Richard Cooper; Keith Briffa (Climate Dynamics, 2013)

Recent summer precipitation trends in the Greater Horn of Africa and the emerging role of Indian Ocean sea surface temperature - A. Park Williams; Chris Funk; Joel Michaelsen; Sara A. Rauscher; Iain Robertson; Tommy H. G. Wils; Marcin Koprowski; Zewdu Eshetu; Neil J. Loader (Climate Dynamics, 2012)

Changes in atmospheric circulation and the Arctic Oscillation preserved within a millennial length reconstruction of summer cloud cover from northern Fennoscandia - Giles H. F. Young; Danny McCarroll; Neil J. Loader; Mary H. Gagen; Andreas J. Kirchhefer; Joanne C. Demmler (Climate Dynamics, 2012)

Climate signals in the ring widths and stable carbon, hydrogen and oxygen isotopic composition of Larix decidua growing at the forest limit in the southeastern European Alps - Polona Hafner; Iain Robertson; Danny McCarroll; Neil J. Loader; Mary Gagen; Roderick J. Bale; Högne Jungner; Eloni Sonninen; Emmi Hilasvuori; Tom Levanič (Trees, 2011)

Spring temperature variability in northern Fennoscandia AD 1693–2011 - Neil J. Loader; Risto Jalkanen; Danny Mccarroll; Anders Moberg (Journal of Quaternary Science, 2011)
A reconstruction of spring (April–May) temperature for northern Fennoscandia developed from the Tornionjoki (Tornio river) long cryophenological record of ice break‐up dates, back to AD 1693, is presented. The record is strongly climatically sensitive and explains 67% of the variance in the instrumental data over the last 150 years. The record exhibits a stepped decrease in the duration of the river's ice cover by 14 days, equivalent to an increase in April–May mean temperature of approximately 2.5°C over the last three centuries. The relationship between the date of ice break‐up, and accumulated daily mean temperatures (>0°C) is investigated. Uncertainty in the observation of ice break‐up is also considered in addition to the potential of this time series for regional climate model validation. Copyright © 2011 John Wiley & Sons, Ltd.

Evidence of changing intrinsic water‐use efficiency under rising atmospheric CO 2 concentrations in Boreal Fennoscandia from subfossil leaves and tree ring δ 13 C ratios - MARY GAGEN; WALTER FINSINGER; FRIEDERIKE WAGNER‐CREMER; DANNY MCCARROLL; NEIL J. LOADER; IAIN ROBERTSON; RISTO JALKANEN; GILES YOUNG; ANDREAS KIRCHHEFER (Global Change Biology, 2011)
Investigating the many internal feedbacks within the climate system is a vital component of the effort to quantify the full effects of future anthropogenic climate change. The stomatal apertures of plants tend to close and decrease in number under elevated CO 2 concentrations, increasing water‐use efficiency (WUE) and reducing canopy evapotranspiration. Experimental and modelling studies reveal huge variations in these changes such that the warming associated with reduced evapotranspiration (known as physiological forcing) is neither well understood or constrained. Palaeo‐observations of changes in stomatal response and plant WUE under rising CO 2 might be used to better understand the processes underlying the physiological forcing feedback and to link measured changes in plant WUE to a specific physiological change in stomata. Here we use time series of tree ring ( Pinus sylvestris L.) δ 13 C and subfossil leaf ( Betula nana L.) measurements of stomatal density and geometry to derive records of changes in intrinsic water‐use efficiency (iWUE) and maximum stomatal conductance in the Boreal zone of northern Finland and Sweden. We investigate the rate of change in both proxies, over the recent past. The independent lines of evidence from these two different Boreal species indicate increased iWUE and reduced maximum stomatal conductance of similar magnitude from preindustrial times (ca. ad 1850) to around ad 1970. After this maximum stomatal conductance continues to decrease to ad 2000 in B. nana but iWUE in P. sylvestris reaches a plateau. We suggest that northern boreal P. sylvestris might have reached a threshold in its ability to increase WUE as CO 2 rises.

A critical evaluation of multi‐proxy dendroclimatology in northern Finland - Danny McCarroll; Mervi Tuovinen; Rochelle Campbell; Mary Gagen; Håkan Grudd; Risto Jalkanen; Neil J. Loader; Iain Robertson (Journal of Quaternary Science, 2011)
Twentieth‐century summer (July–August) temperatures in northern Finland are reconstructed using ring widths, maximum density and stable carbon isotope ratios (δ 13 C) of Scots pine tree rings, and using combinations of these proxies. Verification is based on the coefficient of determination ( r 2 ), reduction of error (RE) and coefficient of efficiency (CE) statistics. Of the individual proxies, δ 13 C performs best, followed by maximum density. Combining δ 13 C and maximum density strengthens the climate signal but adding ring widths leads to little improvement. Blue intensity, an inexpensive alternative to X‐ray densitometry, is shown to perform similarly. Multi‐proxy reconstruction of summer temperatures from a single site produces strong correlations with gridded climate data over most of northern Fennoscandia. Since relatively few trees are required (

The climate sensitivity of Norway spruce [Picea abies (L.) Karst.] in the southeastern European Alps - Tom Levanič; Jožica Gričar; Mary Gagen; Risto Jalkanen; Neil J. Loader; Danny McCarroll; Primož Oven; Iain Robertson (Trees, 2009)

Stable carbon isotope composition of terrestrial leaves: inter‐ and intraspecies variability, cellulose and whole‐leaf tissue difference, and potential for climate reconstruction - Mats Rundgren; Neil J. Loader; Dan Hammarlund (Journal of Quaternary Science, 2003)
Stable carbon isotope analysis of terrestrial plant leaves preserved in Quaternary lake sediments has the potential to provide high‐resolution reconstructions of past climatic conditions. Preferably, δ 13 C measurements should be made on a single leaf component, e.g. cellulose, but this approach is often precluded by limited leaf availability. Previous work suggests that reliable palaeoclimatic information also may be derived from δ 13 C measurements on whole‐leaf tissue, given a similar degree of leaf decomposition between samples. Leaf δ 13 C data for 12 Scandinavian species of dwarf‐shrubs, shrubs and trees, and a comparison of δ 13 C data on recent and late Holocene Salix herbacea leaves, revealed that the δ 13 C signal registered by holocellulose is largely reflected by measurements on whole‐leaf tissue. Holocellulose was found to be consistently enriched in 13 C, although this δ 13 C offset was smaller for subfossil leaves. This supports the use of δ 13 C measurements on whole‐leaf tissue for climate reconstruction, at least for leaves preserved in soft, late Holocene sediments with minimal diagenetic effects. Leaf carbon and nitrogen data on fresh leaves of the same 12 Scandinavian species, and corresponding data on late Holocene Salix herbacea leaves, suggest that the leaf C:N ratio is a suitable indicator of the degree of leaf decomposition. Copyright © 2003 John Wiley & Sons, Ltd.